THE KEYBOARD WAR: EXPLORING BJP VS. CONGRESS RHETORIC ON X DURING THE 2021 ASSAM ASSEMBLY ELECTIONS - Sarma, Debashis Pratim (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper attempts to understand the election rhetoric of the Indian National Congress and the Bharatiya Janata Party in X during the Assam Assembly Election, 2021. The election was marked by intense political rivalry and diverse campaign methods. The growing use of social media has made it crucial for political parties today to establish a positive presence on these platforms. Political parties employ various strategies to appeal to voters in order to achieve this. The study collected X posts from both the Indian National Congress and the Bharatiya Janata Party to analyse the discourse on social media during the Assam Assembly Election, 2021. The posts were analysed and themes were identified utilising the six-step guide by Braun and Clarke. The study found that both political parties endeavoured to undermine each other while seeking to persuade the audience in their favour. The study illustrates a contrast in using X for election discourse between the two political parties. The results contribute to the wider field of political communication by offering valuable insights into the dynamics of electoral campaigns in a region known for its complex identity politics and rapid socio-economic shifts.